ANALYSIS OF POLYMORPHISM OF ORGANELLE DNA TO ELUCIDATE THE PHYLOGEOGRAPHY OF NORWAY SPRUCE IN THE EAST EUROPEAN PLAIN - E. K. Potokina; A. A. Kiseleva; M. A. Nikolaeva; S. A. Ivanov; P. S. Ulianich; A. F. Potokin (Вавиловский журнал генетики и селекции)
The history of Norway spruce distribution in the East European plain is discussed with regard to the results of allele diversity survey of the mitochondrial Nad1 gene, which is maternally inherited, and the chloroplast trnT-trnF region, which is paternally inherited in spruce. The polymorphism of organelle DNAs was examined in 221 genotypes from 28 regions of the former USSR in geographical provenances. Alleles common for the northern Picea abies lineage were detected in accessions originated from the most regions investigated. The Nad1 allele typical for the southern lineage of P. abies was discovered just in spruces originated from Carpathians. The Nad1 allele typical for P. obovata was found in spruces from the Sverdlovsk (Urals) and Krasnoyarsk (Siberia) oblasts. Among the trees analyzed, some had chloroplast DNA sequences (trnT-trnF) assigned to P. abies, others carried cpDNA haplotypes fixed for P. obovata. Analysis of organelle DNA allows revealing the hybrid nature of spruces resulting from cross-pollination of different species.